THE MODERATING ROLE OF ENVIRONMENTAL MUNIFICENCE ON TECHNOLOGY-PERFORMANCE RELATIONSHIP: AN EMPIRICAL EVIDENCE OF INDONESIAN MANUFACTURING FIRMS - LENA ELLITAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2003)
Technology adoption is powerful force for industrialization, increasing productivity, supporting growth, and improving the standards of living. Technology is a critical force for a business organization in a competitive environment, and technology advancement play a vital role in long term profitability. One of the issues raised on the relationship between technology and competitive advantage is whether the relationship is the same for all organization in wealthy (munificence) or poor environment. This study focused on the moderating role of environmental munificence on technology-performance relationship. Data were collected through mailed questionnaires to the CEO of Indonesian manufacturing firms. This study finds that both hard and soft technology have positive impacts on all performance indicators. Furthermore, environmental munificence is found to significantly moderate the relationship between hard technology and manufacturing performance. This study finds that the more munificence the environment, the greater the impact of technology on manufacturing performance.